If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(5/3)*x-(3/4) = 7/12 // - 7/12
(5/3)*x-(3/4)-(7/12) = 0
(5/3)*x-3/4-7/12 = 0
5/3*x-4/3 = 0 // + 4/3
5/3*x = 4/3 // : 5/3
x = 4/3/5/3
x = 4/5
x = 4/5
| 5x+5y+6z-3x+4z-6y= | | 100+8.00h=10.00h | | c=5/9(104-32) | | p=2g+2mforg | | 4x^2-2x-26=0 | | 2x+100=272 | | 6k-18=12-4k | | 2p-8=4-4p | | 2y+3(y-6)=7y-4(y-10) | | 2p-8=13-5n | | 2x-7/4+x=2x+7/2+5 | | 7-4a=5a-20 | | 2x+10=14+3x+3 | | 2x-7/4 | | 3n-27=13-5n | | 0.9x-14=1.7x-18 | | 2x+10=14+3 | | 10x+14=3(3x+4) | | 3n-9=13-5n | | 5x-7y=-9 | | 3x-16= | | -107x-7x=7x+19 | | 24x^2-47+20=0 | | x^2-7s=0 | | x^20-7s=0 | | (x-18)(x^2-36)=0 | | -6x^3-10x^2-6x=0 | | factorx^4+16= | | 12-4*(8-x)=20 | | x^4+16= | | 1/u+6=-6 | | -3(2s-3)-9=-2(7s+7)-2 |